Pengaruh Inklusi Keuangan dan Pembiayaan Bank Syariah Terhadap Ketimpangan Pendapatan Nasional dalam Program Sustainable Development Goals (SDGs) - Asih, Rachma Dwi Tresna; Devi, Abrista; Kartika, Tika (Ikatan Da'i Indonesia, 2024)
Quoted from the official website of the Sustainable Development Program-United Nations (2021) that reducing inequality is the 10th goal of the 17 goals in the SDGs programme, one of whose targets is to progressively achieve and maintain income growth of the bottom 40 percent of the population at a level higher than the national average. This study aims to determine the effect of Financial Inclusion on National Income Inequality and the Effect of Islamic Bank Financing on National Income Inequality. This study uses associative quantitative research, using the Financial Inclusion variable (Islamic Bank Third Party Funds) and the Islamic Bank Financing variable (Islamic Bank Financing) to find out whether there is an influence of these variables on the dependent variable, namely National Income Inequality (Gini Ratio).The data collected is secondary data and time series data. in this study using panel data regression methods processed using Eviews 12 software. The findings of this study are that Financial Inclusion has a positive effect on National Income Inequality and Islamic Bank Financing has a negative effect on National Income inequality. In the variables of Financial Inclusion, Islamic Bank Financing and National Income Inequality, it is recommended to be able to use other indicators that are more diverse and varied in order to reach how far Islamic financial inclusiveness is in Indonesia. and can have a positive impact on the SDGs programme at large for the national and international community.